Development of a web-based student enquiry system: integration of ontology and case-based reasoning. (2nd April 2007) - Kang, Seung Hwan; Lau, Sim Kim
This paper discusses the development of a web-based student enquiry system using techniques in Case-Based Reasoning (CBR) combined with advances in ontology. The system functions as an online enquiry front-desk to allow prospective students to find out if they are eligible for admission to a postgraduate course in an Australian University. Ontology is applied to ensure explicit specifications of concept and definition of terminology can be achieved in the system. CBR technique is applied to achieve the query by applying and adapting past queries.